Pickywo card to improve students’ ability in writing descriptive text - Walida Wahid Fitriani; Silvia N.P. Erito (ELT in Focus, 2024)
The use of media in the teaching-learning process is very helpful. It is like a bridging stuff to communicate between teacher ideas and students. This research had two objectives. Those are to find out the significant improvement of using PICKYWO card in writing descriptive text and to find out the students’ activeness during the research. This research was carried out by using classroom action research. It took two cycles. The research participants were the students in eighth grade of SMP N 2 Sulang. The researchers took class VIIIA as the sample. The researchers used three instruments. Those were writing tests, checklist observation, and questionnaires. The finding showed a significant improvement in students’ average in writing descriptive text from the first and the second cycle. It was from 67,1 to 74,6. Moreover, the students’ activeness also improved. Before conducting the research, students tend to get bored and lazy and complain about having difficulty getting ideas when they are writing descriptive text. In the first cycle, 80% of students actively used the PICKYWO card in writing descriptive classes. Meanwhile, 87,2% of students were active in the second cycle. In short, using PICKYWO card brings significant improvement toward students’ achievements and students’ activeness in writing descriptive.